Income-related mental-health inequality: The effects of the 2008 Icelandic economic crisis - María Erla Bogadóttir 1984- (2011)
Background and aims: Positive health-income gradients are generally accepted. But what happens when an economy collapses? One might expect health to worsen, but recent results indicate that physical health improves in recessions, although the same may not hold for psychological health. The effect of business cycles on income and health has usually been analyzed separately. The aim of this thesis is to observe the effect of the Icelandic economic collapse on income-related health inequality. Data and methods: The data utilized is a panel data that originated from a health and lifestyle survey carried out by The Public Health Institute of Iceland in 2007 and 2009. A stratified random sampling method was used to gather individual-level information about income, self-assessed health and other socio-demographic variables. To evaluate income-related health inequality concentration curves are plotted and concentration indexes computed. The variable used to capture living standard is equivalent household income, before taxes. The variable used to capture health status is self-reported self-perceived morbidity. Results: There seems to be some evidence of income-related health inequality favoring the higher income groups, based on the considered ill-health conditions (difficulty sleeping, serious worries, anxiety or melancholy) measured by whether they disturbed daily life at least once for the past year. However the concentration curve for 2009 is closer to the line of equality indicating less income-related health inequality than in 2007, except for difficulty sleeping. The reason might be higher prevalence of the ill-health conditions for men in higher income groups in 2009 than in 2007 and thus dragging the overall concentration index closer to zero. Bakgrunnur: Skammtíma þættir svo sem breytingar á efnahag geta haft áhrif áhrif á heilsu einstaklinga. Með versnandi efnahag eykst atvinnuleysi, laun geta lækkað og almennt hefur verið talið að heilsa versni í leiðinni. Þó hafa nýlegar rannsóknir bennt til þess að ...